2012
DOI: 10.7762/cnr.2012.1.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Self-Efficacy, and Perceived Barriers on the Low-Iodine Diet among Thyroid Cancer Patients Preparing for Radioactive Iodine Therapy

Abstract: The purposes of the study were to assess knowledge, self-efficacy, and perceived barriers on a low-iodine diet among thyroid cancer patients and to identify strategies for nutrition education. A self-administered questionnaire was developed based on a review of literature and pilot-tested. A total of 121 female thyroid cancer patients participated in a survey and 117 responses were used for data analysis. An average knowledge score of the thyroid cancer patients was 4.5 point (available score: 0-10 point). Maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
4
16
0
Order By: Relevance
“…Over half of the clinicians (53%) indicated that people coped very well with the diet, although some suggested that there are groups of people who struggle and that some people attempt to follow a very restrictive no-iodine diet. Two studies, both conducted in South Korea, reported that people believed the LID to be important but found it difficult to follow because they enjoyed foods high in iodine, struggled to find alternatives and found it difficult to eat outside the home [18,19]. Difficulties with food eaten outside of the home were also reported by people in Brazil [20].…”
Section: Discussionmentioning
confidence: 99%
“…Over half of the clinicians (53%) indicated that people coped very well with the diet, although some suggested that there are groups of people who struggle and that some people attempt to follow a very restrictive no-iodine diet. Two studies, both conducted in South Korea, reported that people believed the LID to be important but found it difficult to follow because they enjoyed foods high in iodine, struggled to find alternatives and found it difficult to eat outside the home [18,19]. Difficulties with food eaten outside of the home were also reported by people in Brazil [20].…”
Section: Discussionmentioning
confidence: 99%
“…Post-thyroidectomy thyroid cancer patients are often placed on low-iodine diets before radioactive iodine (RAI) treatment in order to enhance I-131 uptake and maximize the destruction of cancerous thyroid cells 13 . One study found that among a cohort of Korean females, approximately 37% did not know that fish pastes, hams, and sausages contained high levels of iodine, and 36% over-estimated the amount of dairy they were allowed to consume on a low-iodine diet 14 . It is plausible that Filipino patients have similar misunderstandings and a higher intake of iodine-rich foods, such as seafood and dairy, than other patients preparing for RAI treatment, which may render the treatment less effective, or may modulate tumor behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In areas where the average estimated iodine intake is high, individuals may require a longer length of iodine restriction. Moreover, duration can influence an individual's adherence to iodine restriction, as patients find difficulty implementing and complying with this dietary change due to a low level of knowledge about how to prepare a LID …”
Section: Methodsmentioning
confidence: 99%
“…Strict adherence to a LID may be a source of anxiety for patients and can be time‐consuming for medical staff to implement . A Korean study surveying 117 female patients with thyroid cancer found that they had a low level of knowledge on the food types that are allowed and restricted in a LID . Additionally, patients often mistook the low iodine diet as a low salt diet.…”
Section: Methodsmentioning
confidence: 99%